ANALYSIS OF PARENTS PARENTING STYLES AND STUDENTS LEARNING MOTIVATION - Lili kasmini; Mardhatillah Mardhatillah (Sensei International Journal of Education and Linguistic, 2023)
This study aims to determine the parenting style of parents in motivating children's learning, with the formulation of the problem the role of parenting style towards children in increasing learning motivation. This study used a qualitative descriptive method as a stage in carrying out the research. This research will be carried out by taking the subject of parents and students as research subjects. This study uses data collection techniques including the stages of observation, interviews, and documentation. The data analysis used is descriptive qualitative data analysis. The results of the study show that most parents apply a type of democratic parenting, by applying disciplined learning habits, being independent, and being obedient to worship are able to provide a role for children, especially in learning motivation. The parenting style that is applied to children and is able to motivate children to learn so that they get maximum learning results. Democratic parenting can also form characters in the form of discipline, independence, religion, and communicative.